How to Make an Immune System and a Foreign Host Quickly Cohabit in Peace? The Challenge of Acute Graft-Versus-Host Disease Prevention After Allogeneic Hematopoietic Cell Transplantation - Vandenhove, Benoît; Canti, Lorenzo; Schoemans, Hélène; Beguin, Yves; Baron, Frédéric; Graux, Carlos; Kerre, Tessa; Servais, Sophie (Frontiers in Immunology, 2020)
Allogeneic hematopoietic cell transplantation (alloHCT) has been used as cellular immunotherapy against hematological cancers for more than six decades. Its therapeutic efficacy relies on the cytoreductive effects of the conditioning regimen but also on potent graft-versus-tumor (GVT) reactions mediated by donor-derived immune cells. However, beneficial GVT effects may be counterbalanced by acute GVHD (aGVHD), a systemic syndrome in which donor immune cells attack healthy tissues of the recipient, resulting in severe inflammatory lesions mainly of the skin, gut and liver. Despite standard prophylaxis regimens, aGVHD still occurs in approximately 20-50% of alloHCT recipients and remains a leading cause of transplant-related mortality. Over the past two decades, advances in the understanding its pathophysiology have helped to redefine aGVHD reactions and clinical presentations as well as developing novel strategies to optimize its prevention. In this review, we provide a brief overview of current knowledge on aGVHD immunopathology and discuss current approaches and novel strategies being developed and evaluated in clinical trials for aGVHD prevention. Optimal prophylaxis of aGVHD would prevent the development of clinically significant aGVHD, while preserving sufficient immune responsiveness to maintain beneficial GVT effects and immune defenses against pathogens.